The physiological and genetic bases of water-use efficiency in winter wheat - Baburai Nagesh, Aravinda Kumar (2006)
Winter wheat (Triticum aestivum L.) is the most extensive arable crop in the UK grown on about 2M ha p.a. There is a need to identify traits to ameliorate yield losses to drought which are on average about 15% per year. These losses will be exacerbated with predicted climate change. The overall objectives of the present study were to investigate the physiological and genetic bases of water-use efficiency (ratio of above-ground dry matter production to evapotranspiration; WUE) in winter wheat grown in UK conditions and to quantify relationships between WUE and yield performance under drought.